The Role of External Diagnosis in School Improvement in an Ontario School District - Ross, John A.; Sibbald, Timothy (Alberta Journal of Educational Research, 2011)
External diagnosis is recommended when schools lack the capacity to assess their needs. This qualitative study of one Ontario district compared 33 elementary schools that conducted external diagnosis with 47 schools that used internal diagnosis. External diagnosis created pressure for change, helped schools develop a plan that included previously neglected needs, promoted consistency within and between schools, contributed to the improvement culture of the school, and encouraged shared instructional leadership. It also depressed teacher efficacy and commitment to school improvement. Positive effects of external diagnosis were facilitated and negative effects mitigated by principals who adopted shared instructional leadership strategies. L'on recommande une analyse externe quand les écoles n'ont pas la capacité d'évaluer leurs besoins. Cette étude qualitative d'un district en Ontario porte sur une comparaison entre 33 écoles élémentaires qui ont entrepris un diagnostic externe et 47 écoles qui ont eu recours à un diagnostic interne. Les diagnostics externes ont créé une pression pour le changement, aidé les écoles à développer un projet qui incluait des besoins auparavant négligés, favorisé la cohérence à l'intérieur des écoles et entre elles, contribué à la culture d'amélioration de l'école et encouragé le partage du leadership de l'enseignement. Ils ont également diminué l'efficacité des enseignants et leur engagement face à l'amélioration de l'école. Les effets positifs des diagnostics externes ont été facilités et les effets négatifs mitigés par les directeurs qui ont adopté des stratégies de partage du leadership de l'enseignement.